Giant lipoma of forearm causing median nerve compression – a case report - Rachana DT,; Hrishikesh P. Salgaonkar,; Premashish JH, (Faculty of Medicine, Universiti Kebangsaan Malaysia Medical Centre, 2016)
Giant lipomas in the proximal upper extremity are rare. Traditionally these are slow growing tumour and cause symptoms depending upon their size, position and compression of surrounding structures. Lipoma causing compression of median nerve in the forearm is rare. Surgical excision invariably leads to complete recovery. We present a case of a giant lipoma in forearm causing neuropathy of median nerve. It is difficult to clinically judge the extent of lipoma in atypical position and findings. MRI should be used in pre-operative evaluation of these cases. Surgical excision causes complete resolution of symptoms.